Seasonal comparison of Landsat ETM+ derived land surface temperature for southern Bali - Asmiwyati, I.; Corner, R.; Dewan, Ashraf (2013)
Urban areas consist of various natural semi-natural and manmade surfaces which are related to the urban thermal environment. The retrieval of land surface temperature (LST) from satellite thermal infrared data is affected by strong microclimatic contrasts of temperature that vary with the seasons. However, few studies have been conducted of thermal infrared remote sensing of tropical islands in different seasons. This study investigates the LST over the southern part of the island of Bali which represents typically tropical climatic conditions and land use and land cover (LULC). The variation of LST with different types of LULC was analysed using the Landsat 7 ETM+ thermal bands for May 2002 and March 2003. Results show that, as has been suggested by a previous study, the surface temperature of most types of tropical LULC are insensitive to the change of seasons.